1984
DOI: 10.1007/bf02386232
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bacterial activities in aerobic and anaerobic waste water purification

Abstract: Some aspects of the bacteriology of aerobic and anaerobic waste water purification are discussed in view of current opinions and recent developments in the technology of waste water treatment. Various contributions of scientific workers attached to the Department of Microbiology of the Agricultural University, Wageningen, during the past 65 years are summarized. Besides, present investigations are described and research activities in future indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…In this case, the extracellular soluble phosphate increased from 0.42 to 1.20 mmol/liter, with an initial release rate of 0.15 mmol of Pi per h per g (dry weight) of sludge during the anaerobic phase, and subsequent aerobic treatment resulted in removal of 85% of the soluble phosphate. The P1 release rate in the laboratory sludge was similar to those of other anaerobic-aerobic systems reported elsewhere (17,20) and was considerably higher than those recorded for pure Acinetobacter cultures (1,10,19) and other bacteria (23).…”
Section: Resultssupporting
confidence: 84%
“…In this case, the extracellular soluble phosphate increased from 0.42 to 1.20 mmol/liter, with an initial release rate of 0.15 mmol of Pi per h per g (dry weight) of sludge during the anaerobic phase, and subsequent aerobic treatment resulted in removal of 85% of the soluble phosphate. The P1 release rate in the laboratory sludge was similar to those of other anaerobic-aerobic systems reported elsewhere (17,20) and was considerably higher than those recorded for pure Acinetobacter cultures (1,10,19) and other bacteria (23).…”
Section: Resultssupporting
confidence: 84%
“…1 Most of the microorganisms present in the community are bacteria, but other organisms such as cyanobacteria, fungi, yeasts, algae, and ciliates may play important roles. 2 The microflora utilize organic matter and transform it by means of aerobic metabolism into new microbial biomass, carbon dioxide, water, and minerals. Heukelekian and SchulhofP distinguished two processes in the activated sludge system, i.e., those of oxidation and those of floe formation, and suggested that different microorganisms are involved in each of these processes.…”
Section: The Activated Sludge Processmentioning
confidence: 99%
“…Although it is accepted that microorganisms are directly responsible for the effectiveness and success of the activated sludge treatment process, the complexity of microbiological populations is often underestimated during design of the latter. Full understanding of the ecological, physiological and biochemical activities of the microflora is necessary for optimal control of the process 4 …”
Section: Introductionmentioning
confidence: 99%
“…Full understanding of the ecological, physiological and biochemical activities of the microflora is necessary for optimal control of the process. 4 Wastewater with their high organic content is a suitable medium for a large number of microorganisms including some species of fungi. 5 The main aim of the study was to isolate and identify the fungi present in activated sludge plants with membrane bioreactors (MBRs) under different conditions.…”
Section: Introductionmentioning
confidence: 99%